Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{8}{10}-\frac{9}{12}+\frac{15}{18}-\frac{12}{14}\)
=\(\frac{4}{5}-\frac{3}{4}+\frac{5}{6}-\frac{6}{7}\)
=\(\frac{11}{420}\)
vậy~
a; 0,2.\(\dfrac{15}{36}\) - (\(\dfrac{2}{5}\) + \(\dfrac{2}{3}\)): 1%
= \(\dfrac{1}{12}\) - \(\dfrac{16}{15}\): \(\dfrac{1}{100}\)
= \(\dfrac{1}{12}\) - \(\dfrac{320}{3}\)
= \(\dfrac{1}{12}\) - \(\dfrac{1280}{12}\)
= - \(\dfrac{1279}{12}\)
b; 75% - 1\(\dfrac{1}{2}\) + 0,5 : \(\dfrac{5}{12}\)
= 0,75 - 1,5 + 1,2
= -0,75 + 1,2
= 0,45
c; 1\(\dfrac{3}{15}.0,75-\left(\dfrac{8}{15}+0,25\right)\).\(\dfrac{24}{47}\)
= \(\dfrac{28}{15}\).0,75 - \(\dfrac{47}{60}\).\(\dfrac{24}{47}\)
= \(\dfrac{7}{5}-\dfrac{2}{5}\)
= 1
d; \(\dfrac{32}{15}\): (-1\(\dfrac{1}{5}\) + 1\(\dfrac{1}{3}\))
= \(\dfrac{32}{15}\): (-\(\dfrac{6}{5}\) + \(\dfrac{4}{3}\))
= \(\dfrac{32}{15}\): \(\dfrac{2}{15}\)
= 16
2/x-2/15=-8/15 2/x= -8/15+2/15 => 2/x=-6/15=>2/x=2/-5=>x=-5 Vậy x=-5
-7/15 - -2/15